Karakteristik Ketebalan Optik Aerosol di Bandung - Tuti Budiwati; Sumaryati Sumaryati; Iis Sofiati (Indonesian Journal of Physics, 2001)
We’ve been measured the radiation intensity on the clear by sun photometer model MS-120 with wavelength of λ=368, 500, 675, and 778 nm from 1996 to 1998 in LAPAN-Bandung. The data of intensity of radiation were calculated to become the data of optical depth and atmospheric turbidity. From the calculated results apparently the aerosol optical depth was influenced by the source of pollutant particle and relative humidity. The optical depths of aerosol on the wavelength region 500 nm in 1996, 1997 and 1998 have values 1.080; 0.923 and 0.913 respectively. The magnitude of optical depth of aerosol influence to atmospheric turbidity. The coefficient of atmospheric turbidity on wavelength 500 nm in Bandung has range from 0.25-1.20 during dry season (from June to October) from 1996-1998.